2021
DOI: 10.5324/nje.v29i1-2.4044
|View full text |Cite
|
Sign up to set email alerts
|

Antibacterial use by birth year and birth season in children 0-2 years in Norway

Abstract: Introduction: Consumption of antibacterials in children follows seasonal cycles, and time to first treatment depends on birth season. The aim of this study was to describe dispensing rate, one-year periodic prevalence, and age at first prescription in children aged 0-2 years in Norway.Methods: We used data from the Norwegian prescription database and included all dispensed prescriptions on systemic antibacterials in 2008-2017 during the first three years of life to children born 2005-2014. We calculated age by… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

1
0

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 23 publications
0
2
0
Order By: Relevance
“…While there has been a national decrease in antibacterial dispensing rates in Norway, 31 the current study shows that trends vary between Norwegian municipalities for patients below 3 years of age, with municipalities in which more of the population has received tertiary education showing larger decreases in dispensing rates. Several efforts have been made to reduce antibacterial dispensing rates, notably by updating national guidelines for the use of antibacterials 32 and through intervention campaigns.…”
Section: Discussionmentioning
confidence: 47%
See 1 more Smart Citation
“…While there has been a national decrease in antibacterial dispensing rates in Norway, 31 the current study shows that trends vary between Norwegian municipalities for patients below 3 years of age, with municipalities in which more of the population has received tertiary education showing larger decreases in dispensing rates. Several efforts have been made to reduce antibacterial dispensing rates, notably by updating national guidelines for the use of antibacterials 32 and through intervention campaigns.…”
Section: Discussionmentioning
confidence: 47%
“…Decisions on treatment are made by physicians and parents, which suggests that the healthcare provided to children is dependent on parental socioeconomic status and how they seek healthcare for their children as well as the physician’s prescribing habits and responses to different individuals and social groups. Several studies have identified an association between the high use of antibacterials in young children and an increased risk of chronic disease development later in life,31 39–43 so optimising prescribing practices would seem important for reducing health inequalities in future generations.…”
Section: Discussionmentioning
confidence: 99%